Comparative study of the Far-Eastern Seas and the North Pacific by integral parameters of net zooplankton in the epipelagic layer - Igor V. Volvenko (Известия ТИНРО, 2017)
Species diversity and other integral parameters of zooplankton community in the Japan, Okhotsk, Bering, Chukchi seas and adjacent Pacific waters (total area close to 7.0. 106 km2) are compared on the data obtained in the large-scale surveys conducted by Pacific Fish. Res. Center (TINRO) in 1984-2013. Standard Juday net with mesh size 0.186 mm and mouth area 0.1 m2 was used for sampling. Among four seas, the Chukchi Sea takes the 1st place by abundance (ind./m3) and biomass (mg/m3) of zooplankton, 2nd by species evenness, 3rd by mean size of organisms, and the last by species richness and diversity. The Bering Sea is the 1st by mean size of animals, 2nd by species richness, diversity and biomass, 3rd by abundance, and the last by species evenness. The Okhotsk Sea takes the 2nd place by mean size of zooplankton, the last by its abundance, and the 3rd by other parameters. The Japan Sea is the 1st by species richness, evenness and diversity, 2nd by abundance, and the last by mean size of zooplankton and therefore by its biomass. Zooplankton in the Pacific waters has the lowest abundance, but its biomass is higher there in comparison with the Japan Sea. Species richness is the highest in the Pacific, but species diversity is higher there than in the Chukchi Sea and species evenness is the lowest. Mean size of zooplankton organisms in the Pacific is rather large but smaller than in the Bering Sea. In general, zooplankton abundance increases northward in accordance with nutrients supply, as well as the mean size of animals (with exclusion of the Chukchi Sea), but uniformity of the species abundance has opposite tendency (except the Chukchi Sea again). The rank in biodiversity coincides with the rank in species richness. The latter decreases from south to north (with exclusion of the Okhotsk Sea), but depends strongly on size of the surveyed area and surveyed volume of water. Some unexpected statistically significant relationships are found between the integral parameters of zooplankton and these parameters for pelagic and bottom macrofauna which have not yet any rational interpretation.